A history of crime and the American criminal justice system - Roth, Mitchel P., 1953- author.
1 online resource.
Keywords: This book offers a history of crime and the criminal justice system in America, written particularly for students of criminal justice and those interested in the history of crime and punishment. It follows the evolution of the criminal justice system chronologically and, when necessary, offers parallels between related criminal justice issues in different historical eras. From its antecedents in England to revolutionary times, to the American Civil War, right through the twentieth century to the age of terrorism, this book combines a wealth of resources with keen historical judgement to offer a fascinating account of the development of criminal justice in America. A new chapter brings the story up to date, looking at criminal justice through the Obama era and the early days of the Trump administration. Each chapter is broken down into four crucial components related to the American criminal justice system from the historical perspective: lawmakers and the judiciary; law enforcement; corrections; and crime and punishment. A range of pedagogical features, including timelines of key events, learning objectives, critical thinking questions and sources, as well as a full glossary of key terms and a Who's Who in Criminal Justice History, ensures that readers are well-equipped to navigate the immense body of knowledge related to criminal justice history. Essential reading for Criminal Justice majors and historians alike, this book will be a fascinating text for anyone interested in the development of the American criminal justice system from ancient times to the present day.